(untitled) (Research, Society and Development, 2021)
Caused by the bacterium Mycobacterium tuberculosis, tuberculosis manifests itself through cough considered as the main symptom, in addition to: fever, night sweats, frankness, weight loss, body aches and tiredness. Thus, failure to treat the disease can lead to the spread and resistance of the bacillus that causes the disease. Tuberculosis, despite being an old disease, presents itself as a serious public health problem in Brazil. Thus, the objective of this research was to evaluate the cases of tuberculosis in the city of Almenara-MG between the years 2014 to 2019. It is a theoretical-practical study founded on bibliographic research and simultaneously with a practical study carried out from secondary data obtained from the city of Almenara - MG, from 2014 to 2018. When conducting the research, it was noted that the pulmonary clinical form was the most prevalent. It has a higher prevalence of cases in males and, above all, with low education. Through data from the Notifiable Diseases Information System (SINAN), cases of tuberculosis (TB) were found in people aged over 20 years. This explains why the BCG vaccine is effective.